The relationship between dietary patterns and nutritional status of preschoo-aged children at Dahlia Persatuan Guru Republik Indoensia Kindergarten Madyopuro Village Sumobito - Leny Nur Azizah; Mamik Ratnawati (UPPM STIKES Pemkab Jombang, 2026)
Nutritional status in preschool children is an important indicator for assessing health quality and growth. Nutritional problems among children remain a public health challenge, one of which is influenced by unbalanced dietary patterns. This study aimed to determine the relationship between dietary patterns and the nutritional status of preschool children at TK Dahlia PGRI, Madyopuro Village, Sumobito. This study employed a quantitative correlational analytic design with a cross-sectional approach. The population consisted of 46 preschool children, and all participants were selected using the total sampling technique. Data were collected using questionnaires and analyzed using the Spearman’s Rank statistical test. The results showed that most respondents had good nutritional status (76.1%), and the majority had dietary patterns in the sufficient category (82.6%). The Spearman’s Rank test revealed a p-value of 0.007 (< 0.05), indicating a significant relationship between dietary patterns and nutritional status. The correlation coefficient was r = 0.393, indicating a weak correlation. There is a significant relationship between dietary patterns and the nutritional status of preschool children. Inadequate dietary patterns may negatively affect children's nutritional status. Therefore, nutritional education for parents needs to be improved to support optimal growth and development of children.